Antibacterial and Antibiofilm Activity of Juglone Derivatives against Enterococcus faecalis: An In Silico and In Vitro Approach. (10th November 2022) - Niaz, Falak; Faheem, Muhammad; Khattak, Mutiullah; Khawaja, Iqra Anam; Ahn, Mi-Jeong; Sarker, Umakanta; Jamal, Syed Babar; Ullah, Riaz; Khalil, Atif Ali Khan
Abstract : Enterococcus faecalis is a Gram-positive bacterium that is normally found in the gastrointestinal tract of humans and animals. E. faecalis is an opportunistic pathogen that causes a number of invasive and noninvasive infections. The emergence of multidrug resistance and biofilm formation by the bacterium have rendered the treatment of E. faecalis infections very difficult. Due its high rate of resistance and biofilm formation, there are very few options of treatment. Therefore, the current study was designed to evaluate the antibacterial and biofilm activities of juglone derivatives such as 2-methoxy-6-acetyl-7-methyljuglone and 2-ethoxy-6-acetyl-7-methyljuglone against multidrug-resistant (MDR) and biofilm-producing strains of E. faecalis . Agar well diffusion and broth microdilution methods were used to determine the antibacterial activities. Biofilm attachment and preformed biofilm inhibition were determined using crystal violet staining assay. Both juglone derivatives displayed promising antibacterial and antibiofilm activities against E. faecalis . Among these compounds, 2-ethoxy-6-acetyl-7-methyljuglone possessed better inhibitory activity with minimum inhibitory concentration (MIC) of 9.7 ± 3 μ M as compared to 2-methoxy-6-acetyl-7-methyljuglone (MIC, 19.5 ± 2 μ M ). Additionally, 2-ethoxy-6-acetyl-7-methyljuglone also showed stronger antibiofilm activity than 2-methoxy-6-acetyl-7-methyljuglone. Furthermore, both the ligand molecules were docked into the binding site of the enterococcal surface protein, and the results revealed that both the molecules are actively binding in the target site. Based on these findings, juglone derivatives may be considered useful for the treatment of E. faecalis infections; however, further studies are required to elucidate the mechanism of action.